PENGARUH AROMATHERAPY TERHADAP MUAL DAN MUNTAH PADA IBU HAMIL (SYSTEMATIC RIVEW) - Wellina BR Sebayang (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2021)
Pregnancy is natural process from conceotion to the onset of labor. In pregnancy physiological changes occur in the entire organ system, due to hormonal changes that occur during pregnancy. 50-90% of pregnant women experience nausea in the first trimester. This study uses a systematic review method with the aim to see the effect of aromatherapy on nausea and vomiting in pregnant women.this systematic review reviews 10 journals published through google scoolar’s website.the results of this journal review found 7 aromatherapy that can reduce nausea and vomiting in pregnant women, namely : aromatherapy ginger , lemon ,orange , lavender, steeping peppermint leaves, essential oils of peppermint and ginger oil.